Studi In Silico Potensi Dna Barcode Berdasarkan Gen matK, ITS, dan rbcL Serta Analisis Filogenetik Pada Anggrek Langka Phalaeonopsis - Risah; Miftahul Jannah (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
Orchids are one of the plant groups with abundant species diversity and make a significant contribution to ecosystem functions. Their morphological beauty and high economic value make orchids highly sought after, but this has led to excessive exploitation by the public. One of the rare orchids with important conservation value is the genus Phalaenopsis, or moon orchid, known for its unique characteristics, such as varied colors and patterns. To identify Phalaenopsis, an appropriate method is required, one of which is DNA barcoding. This study aims to analyze the phylogenetic relationships of the Phalaenopsis genus using the matK, rbcL, and ITS gene sequences in silico. The method used is an in silico study utilizing the GenBank database (NCBI). DNA sequences were collected from NCBI by searching for species names and related genes, namely matK, rbcL, and ITS. The collected data were then analyzed using CLUSTAL W to evaluate the similarity between sequences through alignment, identify sequences with potential as barcodes, and reconstruct the phylogenetic tree using MEGA 11. The results showed that alignment with the matK, rbcL, and ITS loci yielded a sufficiently high level of similarity. However, the ITS gene provides more detailed information about the topology of the molecular phylogenetic tree at the species level compared to the matK and rbcL genes. Additionally, the ITS gene can reveal specific characteristics of Phalaenopsis, indicating its potential as a DNA barcode.